(untitled) (MMIT Proceedings, 2026)
This article evaluates the factors affecting profitability indicators in commercial bank operations based on statistical regression analysis. Hamkorbank’s financial indicators for 2020–2024 were selected as the research object. Descriptive statistics, correlation analysis, and multivariate regression modeling were applied. The empirical results showed that total assets, the loan portfolio, and interest income had a positive effect on bank profitability, while an increase in operating expenses reduced profitability. Based on the findings, scientific and practical recommendations aimed at increasing bank profitability were developed.